Role of endoscopic ultrasound and endoscopic-ultrasound-guided fine-needle aspiration in endoscopic biopsy negative gastrointestinal lesions - Okasha, Hussein Hassan (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Many cases of gastrointestinal (GI) tumors as lymphoma, adenocarcinoma, and most of submucosal tumors (SMT) such as gastrointestinal stromal tumor (GIST) and leiomyoma are difficult to diagnose as they frequently yield negative endoscopic biopsies. We evaluated the accuracy of endoscopic ultrasound (EUS) and EUS-guided fine-needle aspiration (EUS-FNA) in the diagnosis of endoscopic biopsy negative GI tumors. PATIENTS AND METHODS: One hundred and nine patients with biopsy negative GI tumors were included in this prospective study. EUS and EUS-FNA were performed to all patients with cytopathologic examination. RESULTS: There were 109 patients with endoscopic biopsy negative GI lesions, including 61 males (56%) and 48 females (44%), with the mean age of 54 years. Sixty-three cases (57.8%) were proved to have malignant lesions, among them there were 15 cases with high-risk GIST as proved by FNA and excision biopsy. Forty-six cases (42.2%) were proved to be benign; among them there were 21 cases presented with non-high-risk GIST. Endoscopic ultrasound had a sensitivity of 96.8%, specificity of 89.1%, positive predictive value (PPV) of 92.4%, negative predictive value (NPV) of 95.3%, and accuracy of 93.6%. EUS-FNA had a sensitivity of 87.3%, specificity of 100%, PPV of 100%, NPV of 85.2%, and accuracy of 92.7%. CONCLUSION: EUS with EUS-FNA is an accurate procedure in the diagnosis of GI tumors with negative endoscopic biopsies.